Impact of Pruning and Agronomical Management on Wood Production and Yield of Paddy under Dalbergia sissoo Roxb. Based Agroforestry System - Patel, Sudha; Bisen, Neelam; Jain, K. K.; Rahangdale, C. P. (International Journal of Bio-resource and Stress Management, 2017)
The field experiment was conducted at the Research Farm, of New Dusty Acre Area, Department of Forestry, College of Agriculture, JNKVV, Jabalpur (M.P.) during, kharif season of 2014. The experiment involve four pruning intensities+one open (without tree) in main plot and Three agronomical management practices in sub plot under strip plot design with five replications. Theresults revealed that, the growth and yield attributing parameters of paddy were significantly varied due to the effect of different pruning treatments and agronomical management practices. Among all the treatments open condition (crop only) produced significantly higher grain and straw yield (24.8 q ha-1 and 37.7 q ha-1, respectively). Under agronomical management system 25% more nitrogen produced significantly higher grain and straw yield (21.6 q ha-1 and 36.2 q ha-1). It was found that the diameter at breast height (Dbh) of tree was significantly influenced by different pruning treatments. 25% pruning recorded significantly higher dbh (23.98 cm). The cylindrical volume and stand biomass of tree significantly influenced by different pruning treatments, 25% pruning recorded significantly higher cylindrical volume (217.27 m3 ha-1) and stand biomass (167301.31 kg ha-1), which was significantly superior to 75% pruning and at pt par with no pruning and 50% pruning. The present study suggested that shade of trees adversely affects growth and yield of crop but silvicultural operation which can reduce tree canopy, facilitated entry of sunlight, pruning is one of them.